Defcon 1 Direct Selling - Gage, Randy (Ascent Audio, 2020)
DEFCON is the US military acronym for "Defense Readiness Condition." DEFCON 1 is reserved only for imminent catastrophic events, like a nuclear war. Luckily, you don't have to fend off missile attacks in direct selling, but you will face some extremely difficult challenges and urgent crises leading your MLM team. It takes much more than a positive attitude and motivational words to be a successful field leader. True leadership requires you to deal with messy, complicated scenarios when there is not always a clear-cut solution. Many of these challenges are caused by factors completely out of your control-from economic, regulatory, and political setbacks, to having top leaders quit, to companies going out of business, and a host of other issues. It's at times like these, when it seems like your team is falling apart, that you must draw upon your resilience, persistence, and character to ride out the storm and lead your team through the chaos. This indispensable resource will enable you to: create a team culture of maximum readiness; deal with toxic leaders and effectively handle conflict resolution; use your leadership to make your team more powerful and build their self-esteem; handle corporate incompetence, poor decisions, and PR crises; and know what to do when you or a team leader leave a company.